Predicting clinical outcomes in a blended care intervention for early psychosis: Acceptance and Commitment Therapy in Daily-Life (ACT-DL) - Bonnier, Rafaël A.; Beames, Joanne R.; Kiekens, Glenn; van Aubel, Evelyne; Schirmbeck, Frederike; de Haan, Lieuwe; Marcelis, Machteld; van der Gaag, Mark; van Winkel, Ruud; van Amelsvoort, Therese; Vaessen, Thomas; Reininghaus, Ulrich; et al. (Translational Psychiatry, 2025)
ACT in Daily Life (ACT-DL) is a blended-care Ecological Momentary Intervention that extends ACT into the daily life of individuals, improving psychotic distress, negative symptoms, and global functioning. However, it remains unclear whether ACT-DL works equally for everyone. We investigated whether moderators (i.e., sociodemographic information, personality, and trauma history) determine clinical outcomes in individuals with early psychosis receiving ACT-DL. Seventy-one participants from the INTERACT trial, using ACT-DL, were analyzed. Outcomes included psychotic distress, negative symptoms, global functioning, and psychological flexibility. Using multivariate-multilevel models, we evaluated the effects of sociodemographics, personality, and childhood trauma across baseline, post-intervention, and six- and 12-month follow-ups. Sociodemographic characteristics and personality predicted clinical outcomes. Higher education demonstrated more substantial improvement in global functioning at 6- (B = 7.43, p = 0.04) and 12-FU (B = 10.74, p = 0.002) compared to lower education. Higher extraversion showed less improvement in negative symptoms at 12-FU (B = 1.24, p = 0.01) and more improvement in global functioning at post-intervention (B = 0.39, p = 0.046) and 6-FU (B = 1.40, p = 0.02) compared to lower extraversion. Higher negative affectivity showed more improvement in negative symptoms at 12-FU (B = −1.59, p = 0.001) and higher psychological flexibility at 12-FU (B = 8.38, p = 0.001) compared to lower negative affectivity. Our findings suggest that while ACT-DL improves clinical outcomes in individuals with early psychosis, the improvement rate is dissimilar for individuals and predictable by baseline characteristics. If replicated, these findings enable precision medicine approaches in allocating ACT-DL for early psychosis.